Comparative study of facilities and obstacles of the exporting mipymes in the state of Guanajuato of Mexico and in the lemon province of Costa Rica. - Peart Harris, Kenishia (2020)
This study aims to compare the main facilities and obstacles faced by exporting MSMEs in theState of Guanajuato, Mexico and the Province of Limón, Costa Rica.An attempt was made to identify if there are similarities or differences between the facilitiesand obstacles presented by the exporting Mipymes of the State of Guanajuato, Mexico and theProvince of Limón, Costa Rica.The study is aimed at anyone who exports or has a desire to export, as it will give them usefultools and information to understand a little the scope of exports in Mexico and Costa Rica.The interview method was used to gather the necessary information with a non-probabilistic orconvenience-driven sample.The following results were obtained by indicator:In lemon, there are micro, small and medium-sized companies, while in Guanajuato there areonly small and medium-sized companies. In Guanajuato and Limón the companies belong to theindustrial and commercial sectors. They have the similarity that they export vegetables. SMEs in the state of Guanajuato began their export activities some time before the LimónMSMEs. The companies have their own capital and present similarities and differences in termsof export challenges, quality standards and the process control mechanisms they use.